Prediction of the thermal bow of rotor based on the measured displacement and temperature - He Peng; Zhaohua Zhou; Jigang Feng; Xiangyu Yu; Zhansheng Liu (International Journal of Distributed Sensor Networks)
The thermal bow of the rotor occurs in the cooling process after the shutdown of the aeroengine. The deflection of the bowed rotor is the primary concern of the research on this problem. The objective of this work is to propose a method to predict the bow shape of the rotor with the measured temperature and displacement in a rotor thermal bow experiment. The experiment was introduced and the variations of the measured temperature and displacement were analyzed. A series of polynomial function was proposed to model the bowed shape of the rotor. The measured temperature and displacement were taken into considered in the constraint equations, with which the coefficients in the polynomial function were obtained. The bow shapes of the rotor at different time in the experiments were analyzed. Results showed that the maximum deflection of the rotor was much greater than the measured displacement at the sections near the rotor support. The forced cooling could reduce the thermal deflection of the rotor quickly. The analysis of the different cases of experiment indicated that the proposed method could predict the bow shape of the rotor with the measured temperature and displacement.